Ride performance of driver's seat suspension system using various dynamics models. (October 2022) - Zhou, Huaxiang; Nguyen, Vanliem; Hua, Wenlin; Zha, Jili; Wang, Shan
The research has proposed three isolation models of the negative-stiffness-element (NSE), the damping-element (DE), and the NSE embedded to the small mass (NSE-SM) that was connected with the seat suspension to ameliorate the ride comfort of the driver. A vibration model of the vehicle and seat built under the random and bumpy excitations has been used for evaluating the isolation performance of the NSE, DE, and NSE-SM. The effect of the NSE, DE, and NSE-SM's dynamic parameters on their isolation performance is then evaluated via the root-mean-square values of the seat displacement ( z ws ) and seat acceleration ( a ws ). Based on the genetic algorithm, the NSE, DE, and NSE-SM's dynamic parameters are optimized to fully reflect their isolation performance. The investigation result indicates that the driver's ride comfort is slightly affected by the geometric dimension ratios of the NSE, DE, and NSE-SM, while the driver's ride comfort is greatly affected by the damping and stiffness parameters; and the damping and stiffness ratios of the NSE, DE, and NSE-SM. With the optimized parameters of the NSE, DE, and NSE-SM, the simulation results under the different operating conditions of the vehicle show that the DE slightly improves the driver's ride comfort. Conversely, both the NSE and NSE-SM greatly improve the driver's ride comfort, especially the NSE-SM. Therefore, the model of the seat suspension embedded by the NSE-SM should be applied for improving the driver's ride comfort.